Optimum utilization of energy consumption in arm robot - Mohd Shah, Hairol Nizam; Kamis, Zalina; Shukor, Ahmad Zaki; Baharon, Mohd Rizuan; Sulaiman, Marizan; Wan Azahari, Wan Nur Farhana (Canadian Center Of Science And Education, 2019)
This paper introduced on how to minimize the energy and performance of arm robot. The objective is to design the optima; performance of the arm robot movement in performing certain tasks. There are three process involved in minimize the energy which are hardware assembly selection, Denavit Haternberg (D-H) parameters and optimization process of robot movements. A 3 degree of freedom ROB0036 robot arm is use as hardware selection. Then determine the Denavit Haternberg (D-H) parameters for robot through theoretical, simulation and practical forward and inverse kinematics. The optimization process involved how to control parameters know as position angle and the speed of motor of three main axes of arm robot. The performance is measured respect to the two movement, which are reference and optimized. The energy efficiency analysis is performs to reduce this energy consumed. The simulation resulted show that the minimum motor’s movement of joint, the less time taken to achieve of to complete the pick and place task. Directly, it results on less energy used and increase the robot arm performance.